Pengaruh Financial Stress dan Career Anxiety terhadap Academic Anxiety pada Mahasiswa (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
College students face various pressures during their studies, such as financial problems and career uncertainty, which can potentially increase academic anxiety. These conditions can interfere with their ability to concentrate on their studies, their academic performance, and their psychological well-being. This study aims to determine the effects of financial stress and career anxiety on academic anxiety among college students. The study employed a quantitative approach involving 1,062 active students enrolled in D1 through S1 programs in Indonesia, selected through non-probability convenience sampling. Data were collected using the Financial stress Scale for Undergraduate Students (FSS-CV), the Career anxiety Scale, and the Academic anxiety Scale (AAS), and were then analyzed using descriptive statistics, Spearman’s Rho correlation test, as well as simple and multiple regression analyses. The results indicate that financial stress has a positive and significant effect on academic anxiety (R² = 0.183; p < 0.05), while career anxiety also has a positive and significant effect (R² = 0.008; p < 0.05). Taken together, these two variables account for 21.8% of the variance (R² = 0.218; p < 0.05), meaning that the higher the levels of financial stress and career anxiety, the higher the students’ academic anxiety.